Application of swine wastewater for irrigation of Tifton 85 grass: Part I-productivity and nutritional quality - Gomes, Eder Pereira; Sanches, Arthur Carniato; Dias, Dhiones Kenedys Ulisses; de Jesus, Fernanda Lamede Ferreira; de Albuquerque Nunes, Walder Antônio Gomes; Orrico, Marco Antônio Previdelli; de Souza Dias, Joelma Porto; Azevedo, Edéria Pereira Gomes [UNESP] (Southern Cross Publishing, 2018)
The use of swine wastewater (SW) for irrigation can be an excellent alternative to increase productivity and quality of pastures. This work was carried out from October 2013 to September 2014 in Dourados - MS. The objectives were evaluation of the productivity and nutritional quality of Tifton 85 grass (Cynodon spp.) under different doses of SW in the presence and absence of normal water irrigation. The experiment was set in a randomized block with split plots design, including water irrigated and non-irrigated in the main plots and four doses of SW in the subplots (75, 150, 225 and 300 m3 ha-1 cut-1), with four replicates. The total forage yield and the bromatological value (crude protein, neutral and fibre detergent acid and dry matter digestibility) were evaluated. There was a significant effect of irrigation and SW doses on total dry matter yield, reaching 41.4 Mg ha-1 year-1 using the highest dose of SW (300 m3 ha-1) and irrigation use. Irrigation also provided higher crude protein levels, increasing with linear adjustment to SW doses, reaching 17.9% in the annual average. The neutral detergent fibre and the acid detergent fibre presented lower results under irrigation, reaching 65.4 and 32.6% in the annual average, respectively, and linearly decreased using SW doses. Inverse behavior was observed in the in vitro digestibility of dry matter, which was higher under irrigation, reaching 69.5% in the annual average and presenting linear growth according to doses of SW.
Keywords: Botanical composition; crude protein; Cynodon spp.; Dry matter yield; Forage quality; organic fertilization